2020
DOI: 10.1017/ipm.2020.84
|View full text |Cite
|
Sign up to set email alerts
|

Youth mental health in the time of COVID-19

Abstract: Abstract Youth Mental Health is a rapidly developing field with a focus on prevention, early identification, treatment innovation and service development. In this perspective piece, we discuss the effects of COVID-19 on young people’s mental health. The psychosocial effects of COVID-19 disproportionately affect young people. Both immediate and longer-term factors through which young people are affected include social isolation, changes to the delivery of therapeutic services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 42 publications
(45 reference statements)
3
120
1
7
Order By: Relevance
“…Particularly, prior research has shown that social isolation is associated with increased rates of depression in children and adolescents (Loades et al, 2020). To date, however, most of the recent scholarship has been either commentary aimed at policy or practice or research (Wang et al, 2020;Liu et al, 2020;Power et al, 2020;Ghosh, Dubey, Chatterjee, & Dubey, 2020;Golberstein, Wen, & Miller, 2020;Mahajan, Kapoor, & Prabhakar, 2020), or cross-sectional empirical studies (see Pisano, Galimi, & Carniglia, Preprint, April 13 2020) (Xie et al, 2020). Importantly, though, there has been rising awareness of the need for a longitudinal and developmental approach to investigating the mental health effects of COVID-19 (Wade et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, prior research has shown that social isolation is associated with increased rates of depression in children and adolescents (Loades et al, 2020). To date, however, most of the recent scholarship has been either commentary aimed at policy or practice or research (Wang et al, 2020;Liu et al, 2020;Power et al, 2020;Ghosh, Dubey, Chatterjee, & Dubey, 2020;Golberstein, Wen, & Miller, 2020;Mahajan, Kapoor, & Prabhakar, 2020), or cross-sectional empirical studies (see Pisano, Galimi, & Carniglia, Preprint, April 13 2020) (Xie et al, 2020). Importantly, though, there has been rising awareness of the need for a longitudinal and developmental approach to investigating the mental health effects of COVID-19 (Wade et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The usual youth-related experiences of attending school in physical classrooms, interacting with peers, engaging in enjoyable social activities and preparing for future careers have been disrupted or modified because of the social distancing rules and fear of contagion. Their psycho-emotional development may be affected by the "new normal" characterized by online classes and extra-curricular school events, restricted movement and socializing, interruptions of key social functions and leisure events, and an unclear perspective for the future (Cao et al, 2020;Power et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All of this suggests that the lack of occupational balance translates into a general shortage of regulatory skills and capacities, with negative effects on health, which can lead to serious illnesses [22][23][24][25]. The feelings of loss of control and loneliness, caused by confinement and social distancing, have increased the incidence of daytime stress, altered sleep patterns [21,[26][27][28], and increased irritability [21], as well as the almost-complete loss of structured occupations (school, work, and training) in young adults, one of the groups most affected by the effects of this situation [29,30]. In addition, adverse situations may encourage new lifestyle demands to exceed the individual's capacities to face them, negatively affecting their health status [14].…”
Section: Introductionmentioning
confidence: 99%